PERBEDAAN ASUPAN PROTEIN, FE, VIT B6, VIT C, DAN STATUS KEK PADA REMAJA PUTRI ANEMIA DAN NON ANEMIA - USDEKA MULIANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Iron deficiency anemia (IDA) is a nutritional problem in young women that needs special attention. Except for lack of iron intake, the cause of anemia is due to lack of micronutrient intake that plays a role in iron metabolism, erythropoiesis, and hemoglobin formation, including vitamin B6 and vitamin C. Another nutritional problem that is often experienced by young women is Chronic Energy Deficiency due to energy intake. less than an ongoing need. The purpose of this study was to determine differences in the nutritional intake of protein, iron, vitamin B6, vitamin C and KEK status in anemic and non-anemic adolescent girls. Data collection was carried out in August-September 2020 on 122 respondents. The amount of nutrient intake was obtained through interviews and the respondent's hemoglobin level was measured using the Hemato Analyzer. The research method is analytic by using a cross sectional approach. The data were analyzed univariately and bivariately with a different test (t-test) Independent. The results showed that the prevalence of anemia in respondents was 17.2%, protein intake was less 58.2%, iron (Fe) intake was less 96.8%, vitamin B.6 intake was less than 85.2%, and vitamin C intake was 93. 4%, and respondents with KEK status 46.7%. As for the results of the different tests, there was no significant difference between the intake of protein, iron, vitamin B6, and vitamin C as well as the LILA of the anemic and non-anemic respondents. It is recommended that related parties conduct socialization of healthy feeding for adolescents. ABSTRAKAnemia defisiensi besi (ADB) merupakan masalah gizi pada remaja putri yang perlu mendapat perhatian khusus. Kecuali kekurangan asupan zat besi, penyebab tejadinya anemia akibat kekurangan asupan mikronutrien yang berperan dalam metabolism zat besi, eritropoesis, maupun pembe ntukan hemoglobin antara lain vitamin B6 dan vitamin C. Masalah gizi lain yang sering dialami oleh remaja putri adalah Kurang Energi Kronis akibat dari asupan energy kurang dari kebutuhan yang berlangsung lama. Tujuan penelitian untuk mengetahui perbedaan asupan zat gizi protein, zat besi, vitamin B 6, vitamin C dan status KEK pada remaja putri anemia dan non anemia. Pengambilan data dilakukan bulan Agustus-September tahun 2020 pada 122 responden. Jumlah asupan zat gizi diperoleh melalui wawancara dan alat ukur kadar hemoglobin responden menggunakan Hemato Analizer. Metode penelitian yang bersifat analitik dengan menggunakan pendekatan cross sectional. Data dianalisis secara univariat dan bivariat dengan uji beda (t-test) Independent. Dari hasil penelitian diperoleh prevalensi responden anemia 17,2%, asupan protein kurang 58,2%, asupan zat besi (Fe) kurang 96,8%, asupan vitamin B.6 kurang 85,2%, dan asupan vitamin C kurang 93,4%, serta responden dengan status KEK 46,7%. Adapun dari hasil uji beda tidak ada perbedaan yang significant antara asupan protein, Fe, vitamin B6, dan vitamin C serta LILA responden yang anemia dan yang tidak anemia. Disarankan agar pihak terkait melakukan sosialisasi pemberian makan yang sehat bagi remaja.